Localized malignant mesothelioma of the pleura: Report of a resected case and review of the literature - Nishi, Hideyuki; Shimizu, Nobuyoshi (Nihon Kokyuki Geka Gakkai zasshi (Kyoto, 1992), 2013)
Background: Localized malignant mesothelioma of the pleura (LMM) is an extremely rare tumor. Moreover, the biologic association between LMM and diffuse malignant mesothelioma of the pleura (DMM) remains unclear. Therefore, standard treatment for LMM has not been established. Case: A 65-year-old man who had a history of asbestos exposure was referred to our center because of cough and an abnormal mass shadow in the upper field of the left lung on plain chest radiograph. Computed tomography and magnetic resonance imaging revealed a mass about 7 cm in diameter with a smooth margin and heterogeneous inner structure in the left chest wall. Histologic examination after a fine needle biopsy of the tumor showed an epithelial type of mesothelioma. We considered it to be a localized tumor based on FDG-PET and thoracoscopic findings. Surgery was performed for total removal of the tumor, together with resection of the chest wall. The tumor relapsed at the left chest wall after the operation, and radio-chemotherapy was performed. Conclusion: We reported a case of LMM treated primarily by radical resection, which subsequently relapsed. The relapsed disease was considered to be an isolated dissemination, and different from DMM. According to previous reports, the prognosis of LMM is better than that of DMM. Further studies of the pathologic behavior and establishment of standard treatment are clearly warranted.